A road towards 25% efficiency and beyond: perovskite tandem solar cells. Issue 4 (17th August 2016) - Todorov, T.; Gunawan, O.; Guha, S.
Abstract : For decades, the appealing potential of tandem solar cells for efficiencies beyond the single-junction Shockley–Queisser limit has led researchers to develop thin film tandem solutions for high performance low cost solar cells. Abstract : For decades, the appealing potential of tandem solar cells for efficiencies beyond the single-junction Shockley–Queisser limit has led researchers to develop thin film tandem solutions for high performance low cost solar cells. Perovskite solar cells have recently emerged as a promising candidate for photovoltaics. In addition to ease of fabrication and good efficiencies, a particularly attractive feature is their tunable band gap between 1.48 and 2.3 eV that enables symbiosis with other solar cells in tandem device configurations. The low-temperature processing conditions of perovskites make it possible to monolithically integrate them as the top component of tandem structures without damaging the bottom cell. Early experimental results and modelling indicate that efficiencies beyond 25% are within reach. Optimization and solving perovskite stability limitations could result in a commercially viable technology. We review recent developments and insights in the field.